Modelling blue and green water availability under climate change in the Beninese Basin of the Niger River Basin, West Africa - LAWIN, AGNIDÉ EMMANUEL; BADOU, D. Félicien; Diekkrüger, Bernd; Kapangaziwiri, Evison; Mbaye, Mamadou Lamine; Yira, Yacouba; Oyerinde, Ganiyu Titilope; AFOUDA, ABEL (My University, 2018)
The aim of this study was to quantify climate change impact on future blue water (BW) and green water (GW) resources as well as the associated uncertainties for 4 subbasins of the Beninese part of the Niger River Basin. The outputs of 3 regional climate models (HIRHAM5, RCSM, and RCA4) under 2 emission scenarios (RCP4.5 and RCP8.5) were downscaled for the historical period (1976–2005) and for the future (2021–2050) using the Statistical DownScaling Model (SDSM). Comparison of climate variables between these 2 periods suggests that rainfall will increase (1.7% to 23.4%) for HIRHAM5 and RCSM under both RCPs but shows mixed trends (−8.5% to 17.3%) for RCA4. Mean temperature will also increase up to 0.48 °C for HIRHAM5 and RCSM but decrease for RCA4 up to −0.37 °C. Driven by the downscaled climate data, future BW and GW were evaluated with hydrological models validated with streamflow and soil moisture, respectively. The results indicate that GW will increase in all the 4 investigated subbasins, whereas BW will only increase in one subbasin. The overall uncertainty associated with the evaluation of the future BW and GW was quantified through the computation of the interquartile range of the total number of model realizations (combinations of regional climate models and selected hydrological models) for each subbasin. The results show larger uncertainty for the quantification of BW than GW. To cope with the projected decrease in BW that could adversely impact the livelihoods and food security of the local population, recommendations for the development of adequate adaptation strategies are briefly discussed.
Keywords: adaptation; climate change; interquartile range; statistical downscaling; uncertainty; water; resources